TINJAUAN YURIDIS TERHADAP PENANGANAN PERKARA ANAK DIBAWAH UMUR MELALUI UNIT PERLINDUNGAN PEREMPUAN DAN ANAK BERDASARKAN PERATURAN KEPOLISIAN NEGARA REPUBLIK INDONESIA NOMOR 10 TAHUN 2007 TENTANG ORGANISASI DAN TATA KERJA UNIT PELAYANAN PEREMPUAN DAN ANAK DI LINGKUNGAN KEPOLISIAN NEGARA REPUBLIK INDONESIA - Wulandari, Septiana; Indra, Mexsasai; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Children are the forerunners of youth. Therefore, the handling of children who are in conflict with the law should not lead to stigmatization and lack or even lack of coaching towards them so that their hopes to become young people can be useful to their nation. Referring to this, it is important to agree on the child safety model that is in conflict with the law and children who are in conflict with the law. One form of special protection for children as perpetrators of crime is to establish a Women's and Children's Services Unit (PPA Unit), which was formed based on the Regulation of the Chief of the Republic of Indonesia State Police Number 10 of 2010 concerning the Organization and Work Procedure of the Women's and Children's Services Unit (PPA Unit ) in the Indonesian National Police Environment. The purpose of writing this thesis, namely: first, the legal obligations towards the handling of cases of minors at the Police Level, second, the validity of handling cases of minors carried out by Investigators outside the Protection Unit for Women and Children.This type of research used in this study is normative legal research or can be called doctrinal law research. In this normative legal research, the writer conducts a research on legal synchronization, by conducting an identification in advance of the legal principles that have been formulated in the legislation. Sources of data used, primary data, secondary data, and tertiary data, data collection techniques in research with literature review.From the results of the research problem there are three main things that can be concluded. First, the legal obligation towards handling cases of minors at the Police Level is carried out by child investigators namely the protection unit for women and children, this is regulated in Article 26 of Law Number 11 Year 2012 Concerning the Child Criminal Justice System and Police Regulation Number 10 of 2007 concerning Organization and Work Procedure of Women and Children Service Units in the Indonesian National Police Environment. Second, the validity of handling cases of minors carried out by Investigators outside the Women's and Children's Services Unit handling cases of children is legal based on the provisions of Article 26 paragraph (4) of Law Number 11 of 2012 concerning the juvenile justice system and Article 10 of Police Regulations Number 10 Year 2007 concerning the Organization and Work Procedure of Women and Children Service Units in the Republic of Indonesia National Police Environment.Keywords: Child-Handling-Child Case-PPA Unit